Of memory and the misplaced: Irish immigrant life writing in the United States - O'Brien, Sarah (Irish culture, memory, place, 2023)
"What can the life writing of post-famine Irish immigrants tell us about Irish diasporic memory? Of Memory and the Misplaced draws from the writing of previously unknown immigrants to contest conventional narratives about the Irish in North America. Analyzing over 30 memoirs written between 1900 and 1970, Sarah O'Brien demonstrates how ordinary immigrants subverted the typical grand narratives of Irish nationalism to tell their own story, on their own terms. Using cultural history and linguistics, O'Brien highlights US influence on Irish immigrants, who were able to explore taboo themes such as domestic violence, same-sex love, and famine-induced trauma. Importantly, Of Memory and the Misplaced also critiques the romanticized idea of the Irish landscape as a site of cultural memory and shows how the interiority of the domestic world provided women with the language needed to reclaim their own lives. By combining literary and historical theory with memory studies, Of Memory and the Misplaced highlights voices that have traditionally been silenced and offers a rare and unexplored collection of primary source autobiographical texts to better understand the experiences of Irish immigrants in the United States"--